CHARACTERISTICS OF AMBLIOPIA IN ANISOMETROPIC PATIENTS AT EYE POLYLINIC SANGLAH GENERAL HOSPITAL DENPASAR - Ni Putu Pradita Dhriti Indriyani Sukadan (Institute for Research and Community Services Udayana University, 2018)
The purpose of this cross sectional study was to determine the characteristics of amblyopia in anisometropic patients at Eye Polyclinic Sanglah General Hospital Denpasar.The data hat obtained are secondary data derived from medical records of refractive error in anisometropic patients on April 2016-August 2017 period, and involved 62 patients as research subjects based on consecutive sampling.The results of this study showed that from 62 anisometropic patients, there were 56 patients (90%) affected amblyopia. Based on the sociodemographic aspect, the highest number of patients with amblyopia in the children age group were 24 peoples (43%), females more than males were 37 peoples (66%), the majority of patients living in Denpasar were 28 peoples (50%), and the students were the most type of occupationin amblyopic patients is 35 peoples (63%). Patients with severe anisometropia were 24 peoples (43%), moderate amblyopia at 48 eyes (43%), and affected on both eyes (ocular dextra sinistra) about 35 peoples (63%). The type of refractive error was found to be at most is astigmatism about 74 eyes (66%), and the use of spectacles in 51 people (91%).Based on this research, it can be concluded that subject who were affected amblyopia in anisometropic patients most at age children, female, living in Denpasar, and as students. Severe anisometropia, moderate amblyopia, affected on both eyes, astigmatism, and the uses of spectacles were found to be the most of the subject.